La función de la Corte Penal Internacional y las teorías críticas del derecho internacional - Urueña-Sánchez, Mario (2021)
This article seeks to analyze the function of the International Criminal Court (ICC) from the analytical horizon of critical studies and the particular contributions of the Helsinki School and social idealism. To achieve this objective, the main postulates of both perspectives are compared towards the concept of international criminal justice (ICJ), in general, and towards the performance of the ICC in its time of validity, in particular. The methodology used is that of a documentary analysis with a strong inclination towards texts of a theoretical, doctrinal and jurisprudential nature.